Position control of antenna emitter using PID digital controller - Lai, Wen Hong (2020)
The main purpose of this project is to model simulation of antenna system with PID controller. This project covers the knowledge of control system engineering and the technique of using MATLAB software. Inside the control system engineering part, there is a design process of control system which guides system developers to a right way of designing. This project focuses more on the sixth step of design process, the implementation of PID controller is one of the challenges in the section of sixth step, to yield stability of antenna system. There are many requirements taken based on time and frequency domain during the analysis of PID controller functioning on antenna system. Conversion of analogue into digital antenna system is last process of this project. The MATLAB software is a useful tool of designing and simulating control system. In order to learn how to achieve the system balance, the primary key is to master the relevant graph plots which are very significant to estimate the system behaviour. This project emphasises the time domain standard, it has to be understood as it will help designers on determining gain needed, finding system stability and contributing on PID controller tuning, along the whole progression of this project. The outcome of this project is the simulation results showing that the PID controller successfully improves the transient response and maintain zero steady state error, of the digital antenna system.